Proceedings of the 5th International Conference on Frontiers in Intelligent Computing: Theory and Applications FICTA 2016, Volume 1 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Udgata, Siba K.; Pattnaik, Prasant Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
The book is a collection of high-quality peer-reviewed research papers presented at International Conference on Frontiers of Intelligent Computing: Theory and applications (FICTA 2016) held at School of Computer Engineering, KIIT University, Bhubaneswar, India during 16 - 17 September 2016. The book presents theories, methodologies, new ideas, experiences and applications in all areas of intelligent computing and its applications to various engineering disciplines like computer science, electronics, electrical and mechanical engineering.
Chapter 1. Human Action Recognition Using Trajectory Based Spatio-Temporal Descriptors -- Chapter 2. Mathematical Modeling of Specific Fuel Consumption Using Response Surface Methodology for CI Engine Fueled with Tyre Pyrolysis Oil and Diesel Blend -- Chapter 3. Ensemble Learning for Identifying Muscular Dystrophy Diseases Using Codon Bias Pattern -- Chapter 4. Basic Arithmetic Coding Based Approach to Compress a Character String -- Chapter 5. Comparative Analysis of different Feature Ranking Techniques in Data Mining based Android Malware Detection -- Chapter 6. Feature Optimality Based Semi-Supervised Face Recognition Approach -- Chapter 7. Fuzzy Based Algorithm for Resource Allocation -- Chapter 8. Agreement-Based Interference-Aware Dynamic Channel Allocation in Cognitive Radio Network (CRN) -- Chapter 9. Energy Efficient Resource Allocation for Heterogeneous Workload in Cloud Computing -- Chapter 10. Accent RecognitionSystem Using Deep Belief Networks for Telugu Speech Signals -- Chapter 11. Text Document Classification with PCA and One-Class SVM -- Chapter 12. Data Mining Approach to Predict and Analyze the Cardiovascular Disease -- Chapter 13. A Hybrid Genetic Algorithm for Cell Formation Problems Using Operational Time -- Chapter 14. Efficient and Parallel Framework for Analyzing the Sentiment -- Chapter 15. Content Aware Video Retargeting by Seam Carving -- Chapter 16. Intelligence System Security Based on 3D Image -- Chapter 17. PDA-CS: Profile Distance Assessment Centric Cuckoo Search for Anomaly Based Intrusion Detection in High Speed Networks -- Chapter 18. Evaluation of Barriers of Health Care Waste Management in India - A Grey Relational Analysis Approach -- Chapter 19. Privacy Preserving Association Rule Mining Using Binary TLBO for Data Sharing in Retail Business Collaboration -- Chapter 20. Performance analysis of Compressed Sensing in Cognitive Radio Networks -- Chapter 21. Robust Multiple Composite Watermarking Using LSB Technique -- Chapter 22. FOREX Rate Prediction: A Hybrid Approach Using Chaos Theory and Multivariate Adaptive Regression Splines -- Chapter 23. Gray Scale Image Compression Using PSO with Guided Filter and DWT -- Chapter 24. Graph Partitioning Methods -- Chapter 25. Smart and Accountable Water Distribution for Rural Development -- Chapter 26. Adaptive Huffman Coding Based Approach to Reduce the Size of Power System Monitoring Parameters -- Chapter 27. Color Image Visual Cryptography Scheme with Enhanced Security -- Chapter 28. A Comparative Analysis of PWM Methods of Z-Source Inverters Used for Photovoltaic System -- Chapter 29. Fault Mitigation in Five-Level Inverter Fed Induction Motor Drive Using Redundant Cell -- Chapter 30. A Web-of-Things Based System to Remotely Configure Automated Systems Using a Conditional ProgrammingApproach -- Chapter 31. On the Security of Chaos Based Watermarking Scheme for Secure Communication -- Chapter 32. Neighborhood Topology to Discover Influential Nodes in a Complex Network -- Chapter 33. Venn Diagram Based Feature Ranking Technique for Key Term Extraction -- Chapter 34. Bangla Handwritten City Name Recognition Using Gradient Based Feature -- Chapter 35. Shortest Path Algorithms for Social Network Strengths -- Chapter 36. Improvised Symbol Table Structure -- Chapter 37. Digital Watermarking Using Enhanced LSB Technique -- Chapter 38. Fuzzy-based Adaptive IMC-PI Controller for Real-time Application on a Level Control Loop -- Chapter 39. Face Recognition Using PCA and Minimum Distance Classifier -- Chapter 40. A Soft Computing Approach for Modeling of Non Linear Dynamical Systems -- Chapter 41. Optimization of Workload Scheduling in Computational Grid -- Chapter 42. Cloud Security and Jurisdiction: Need of the Hour -- Chapter 43. A Modified Genetic Algorithm Based FCM Clustering Algorithm for Magnetic Resonance Image Segmentation -- Chapter 44. Skill Set Development Model and Deficiency Diagnosis Measurement Using Fuzzy Logic -- Chapter 45. A Study on Various Training Programmes and their Effects Offered by the IT Firms -- Chapter 46. Analysis of Trustworthiness and Link Budget Power under Free Space Propagation Path Loss in Secured Cognitive Radio Ad-hoc Network -- Chapter 47. A Secure and Lightweight Protocol for Mobile DRM Based on DRM Community Cloud (DCC) -- Chapter 48. Cloud Based Malware Detection Technique -- Chapter 49. Abnormal Network Traffic Detection Using Support Vector Data Description -- Chapter 50. Real Time Automotive Engine Fault Detection and Analysis Using BigData Platforms -- Chapter 51. Load Flow Analysis of Distribution System by Using Artificial Neural Networks -- Chapter 52. An Enhanced Bug Miningfor Identifying Frequent Bug Pattern Using Word Tokenizer and FP-Growth -- Chapter 53. Implementing Anti Malware as Security-as-a-Service from Cloud -- Chapter 54. Recognize Online Handwritten Bangla Characters Using Hausdorff Distance Based Feature -- Chapter 55. A Framework for Dynamic Malware Analysis Based on Behavior Artifacts -- Chapter 56. Evaluation of Machine Learning Approaches for Change-Proneness Prediction Using Code-smells -- Chapter 57. Snort Rule Detection for Countering in Network Attacks -- Chapter 58. Trust and Energy Efficient Routing for Internet of Things - Energy Evaluation Model -- Chapter 59. READ - A Bangla Phoneme Recognition System -- Chapter 60. Information Fusion in Animal Biometric Identification -- Chapter 61. Small World Network Formation and Characterization of Sports Network -- Chapter 62. UWB BPF with Notch Band for Satellite Communication using Pseudo Interdigital Structure -- Chapter 63. Finding Clusters of Data: Cluster Analysis in R -- Chapter 64. A Quality-Concordance Metric Based Contour Detection by Utilizing Composite-Cue Information and Particle Swarm Optimization -- Chapter 65. Analysis of Pancreas Histological Images for Glucose Intolerance Identification Using Wavelet Decomposition -- Chapter 66. A Systematic Review on Materialized View Selection -- Chapter 67. SQLI Attacks: Current State and Mitigation in SDLC -- Chapter 68. Theoretical Validation of Object Oriented Metrics for Data Warehouse Multidimensional Model -- Chapter 69. Paving the Future of Vehicle Maintenance, Breakdown Assistance and Weather Prediction Using IoT in Automobiles -- Chapter 70. Cognitive Architectural Model for Solving Clustering Problem -- Chapter 71. Action Classification Based on Mutual Difference Score -- Chapter 72. Preprocessing and Feature Selection Approach for Efficient Sentiment Analysis on Product Reviews -- Chapter 73. BDN: Bio Degradable Node, Novel Approach for Routing in Delay Tolerant Network -- Chapter 74. Minimization of Energy Consumption Using X-Layer Network Transformation Model for IEEE 802.15.4-Based MWSNs -- Chapter 75. An Automated Approach to Prevent Suicide in Metro Stations -- Chapter 76. B-Secure: A Dynamic Reputation System for Identifying Anomalous BGP Paths -- Chapter 77. Active Steganalysis on SVD Based Embedding Algorithm -- Chapter 78. Handwritten Mixed-Script Recognition System: A Comprehensive Approach -- Chapter 79. A Rule-Based Approach to Identify Stop Words for Gujarati Language.
Keywords: Computational intelligence; Artificial intelligence; Dynamics; Nonlinear theories; Computational Intelligence; Artificial Intelligence; Applied Dynamical Systems